2022
DOI: 10.1021/acs.macromol.2c00181
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Scope of RAFT Multiblock Copolymer Synthesis Using the Nanoreactor Concept: The Critical Importance of Initiator Hydrophobicity

Abstract: Precise multiblock copolymer synthesis coupled with self-assembly offers morphology control on length scales ranging from a few nanometers to micrometer scale, providing enormous opportunities for future development of advanced materials and applications. The scope of multiblock copolymer synthesis via RAFT polymerization has recently been expanded by application of the nanoreactor concept for emulsion polymerization. This enabled use of slow propagating monomers, such as styrenes and methacrylates, in multibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 79 publications
(126 reference statements)
0
24
0
Order By: Relevance
“…It has recently been shown that the use of hydrophilic initiators in emulsion polymerisation can reduce radical penetration of polymer particles, particularly when the particles possess glass transition temperatures higher than the temperature of the reaction ( pMMA T g ≈ 100 °C, 53 T R = 70 °C). 54 Previous studies have noted that whilst the plasticising effect of unreacted monomer may lower the T g inside the particles, this effect is not considered significant enough to have a large influence on radical penetration. 54,55 Reduced radical penetration may reduce access of radicals to RAFT functionality contained within the particles, and therefore decreases the ability of RAFT agents to control the polymerisation.…”
Section: Paper Polymer Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been shown that the use of hydrophilic initiators in emulsion polymerisation can reduce radical penetration of polymer particles, particularly when the particles possess glass transition temperatures higher than the temperature of the reaction ( pMMA T g ≈ 100 °C, 53 T R = 70 °C). 54 Previous studies have noted that whilst the plasticising effect of unreacted monomer may lower the T g inside the particles, this effect is not considered significant enough to have a large influence on radical penetration. 54,55 Reduced radical penetration may reduce access of radicals to RAFT functionality contained within the particles, and therefore decreases the ability of RAFT agents to control the polymerisation.…”
Section: Paper Polymer Chemistrymentioning
confidence: 99%
“…54 Previous studies have noted that whilst the plasticising effect of unreacted monomer may lower the T g inside the particles, this effect is not considered significant enough to have a large influence on radical penetration. 54,55 Reduced radical penetration may reduce access of radicals to RAFT functionality contained within the particles, and therefore decreases the ability of RAFT agents to control the polymerisation. This can result in polymer particles with higher levels of dispersity and may be the reason for the high molecular weight shoulder and broad dispersity seen for these samples.…”
Section: Paper Polymer Chemistrymentioning
confidence: 99%
“…52 Given that the multiblock is a homopolymer of PS, which has a high T g , 73 potential issues with slow radical penetration must be considered. In our recent work, 52 we demonstrated that the use of an oil-soluble initiator can overcome radical penetration issues resulting in well-defined multiblock copolymer via sequential RAFT emulsion polymerization. AIBN is able to overcome radical penetration due to radical formation occurring within the particles instead of in the aqueous phase as for KPS.…”
Section: Multiblock Copolymer Synthesismentioning
confidence: 99%
“…To implement RAFT in emulsion polymerisation, it has been demonstrated that a macroRAFTmediated approach avoids the poor control and colloidal stability often seen in ab initio RAFT emulsion polymerisations. [42][43][44][45][46] Amphiphilic macroRAFT approaches have been widely used to synthesize high molecular weight multiblock copolymers, 15,[36][37][38][39][47][48][49][50][51][52] including multiblock copolymers of low k p monomers such as styrene and methacrylates. Amphiphilic approaches rely on an amphiphilic diblock synthesized in a two-step solution polymerization, that self-assembles in water.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] The combination of miniemulsions with controlled radical polymerizations is particularly attractive due to the higher polymerization rates and minimized termination observed when compared to traditional solution polymerizations. [8][9][10][11][12][13] Another unique property of an ideal miniemulsion polymerization is the so-called 1 : 1 copy feature whereby each monomer nanodroplet is transformed to one polymeric nanoparticle of a similar size. [14][15][16][17] Miniemulsions require high energy input to trigger their formation.…”
Section: Introductionmentioning
confidence: 99%